Community politics, representation and the limits of deliberative democracy - Meadowcroft, John (2001)
Community Politics has been a political strategy of the Liberal Party, now the Liberal Democrats, since 1970. It involves a critique of traditional representational relationships and argues for a participatory democracy based upon deliberation to build consensus out of competing interests. Whilst the associated campaigning techniques have made the third party an important force in local government, this article uses new empirical evidence to assess the success of the strategy in transforming representational relationships and extending popular participation in local government. It is argued that its success in respect of these objectives has been limited, principally because of popular disenchantment with political parties and the inherent tensions and limitations that accompany popular participation in deliberative democratic structures. - Reproduced
Keywords: Local government